COUMARINS FROM BROSIMUM-GAUDICHAUDII - Vilegas, Wagner [UNESP]; Pozetti, G. L.; Vilegas, JHY (Amer Soc Pharmacognosy, 1993)
The new coumarin, (+)-(2'S,3'R)-3-hydroxymarmesin [1], was isolated from the aqueous fraction of the EtOH extract of the root bark of Brosimum gaudichaudii (Moraceae).